Understanding pseudopapilledema on spectral domain optical coherence tomography - Shikha Talwar Bassi; Ramesh Pamu; Anjaly Varghese (Indian Journal of Ophthalmology, 2023)
Purpose: Optic nerve head drusen (ONHD), peripapillary hyperreflective ovoid mass-like structures (PHOMS), and horizontal hyperreflective lines (HHL) are commonly seen in eyes with pseudopapilledema on enhanced depth imaging (EDI) spectral domain optical coherence tomography (SDOCT). The objective of this study is to assess the frequency of ONHD, PHOMS, and HHL on spectral domain OCT in the eyes diagnosed to have pseudopapilledema. Methods: A retrospective case–control study included patients diagnosed as pseudopapilledema and had EDI SD OCT imaging of the optic nerve head (n = 48 eyes) and controls (n = 20 eyes). OCT scans through the optic nerve head were studied to diagnose ONHD, HHL, and PHOMS. One proportion z test was used to find the difference in proportions. Results: Forty eight eyes of 27 subjects were studied. ONHD as described by the optic disc drusen Studies consortium was noted in 19 eyes (39.48%), P value-0.032, PHOMS in 31 eyes (64.6%), P value 0.043, HL in 19 eyes (39.48%), P value 0.032, and none of the normals had ONHD, PHOMS, and HHL. Conclusions: PHOMS are more frequently seen than ONHD and HHL in eyes with pseudopapilledema.